PENDOKUMENTASIAN PERMAINAN RAKYAT DAN OLAHRAGA TRADISIONAL SEBAGAI BAGIAN DARI KEKAYAAN BUDAYA DAERAH BATU URIP KOTA LUBUKLINGGAU - Wawan Syafutra; Hengky Remora; Ever Sovensi (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2022)
Recently, Batu Urip has been designated as a cultural village by the Lubuklinggau city government, this is because Batu Urip is a resident or native of the city of Lubuklinggau. Batu Urip has a variety of traditions that have been passed down from generation to generation from the ancestors to the present, including the tradition of alms, bathing kasai, gaps, berejong, bepanton, nandai, dance, naek yang kule and traditional games. The traditional games owned by the Batu Urip community are very diverse in their forms of play, including terpa hayak, pana teropa, satulage, betu goreng, ijat kemeleng, beteng, pistol bolo, rekek, banana stem beranyot, nyoknyen, taji ijat dian, boor, tekar, yekye, powder ijat para, tire racing, bedel bolo, ope racing, bras, gun let's, kites, bedel pelpa banana, wayang, yakyun, mbukmbang, geseng, yoyok, coket, moyen betu and many other games. This service is carried out in various stages, firstly providing direction to children who will later be used as samples for documentation, then explaining and providing game material that will be documented. Then practice the game that will be documented. We hope that everyone and from every region in Indonesia will take part in preserving cultural heritage in the form of folk games and traditional sports in each region.